Bioavailability of curcumin from a novel mouth dissolving lozenge - Menon, Sasikumar; Mhatre, Mandar; Rajarshi, Manjusha; Thakkar, Jatin (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Cucurmin is the main component of curcuminoids in turmeric (Curcuma longa). Turmeric, popularly used as food colourant, is traditionally used as a medicinal herb owing to its antioxidant, anti-inflammatory, antimicrobial and anticancer properties. The gastric absorption of curcumin is poor and therefore various forms like encapsulation in liposomes, polymeric nanoparticles, cyclodextrin encapsulation, lipid complexes, polymer-curcumin complex etc. have been evaluated. Methods: In the current study, a novel lozenge of 100mg turmeric extract in mouth dissolving formulation is evaluated for bioavailability of curcumin as compared with the conventional hard gelatin capsule containing 475mg curcumin. Fourteen healthy male subjects of Indian origin are dosed in a two way, two treatments, two sequence cross-over balanced, randomized design. Blood samples are collected sequentially to cover the plasma concentration-time curve to obtain a reliable estimate of the extent of absorption. Blood plasma is processed and analyzed using a validated isocratic HPLC-MS/MS method to estimate the concentration of curcumin. Results: Curcumin is detected at m/z 369à177, while the internal standard diazepam is detected as m/z 285à193 to quantify curcumin. Results indicate a significant increase in bioavailability of curcumin from the lozenge (Cmax188.863±22.9620ng/ml; AUC0-t 897.026±65.4844ng/mL*hr) as compared to the hard gelatin capsule (Cmax 96.458±15.8272ng/ml; AUC0-t 440.744±77.3470ng/ml*hr). Conclusions: Mouth dissolving lozenge could be a pragmatic approach to circumvent the low bioavailability of curcumin from therapeutic formulations.